2020
DOI: 10.1002/hep.31230
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Free Virus‐Host Chimera DNA From Hepatitis B Virus Integration Sites as a Circulating Biomarker of Hepatocellular Cancer

Abstract: BaCKgRoUND aND aIMS: Early recurrence of hepatocellular carcinoma (HCC) after surgical resection compromises patient survival. Timely detection of HCC recurrence and its clonality is required to implement salvage therapies appropriately. This study examined the feasibility of virus-host chimera DNA (vh-DNA), generated from junctions of hepatitis B virus (HBV) integration in the HCC chromosome, as a circulating biomarker for this clinical setting. appRoaCH aND ReSUltS: HBV integration in 50 patients with HBV-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 41 publications
1
47
0
Order By: Relevance
“…147 (C) PCR-based CRISPR-Cas13a system. 171 (D, E) A highly efficient microfluidic droplet-based platform to screen single virus particles for optimum vaccine candidate antigenic compounds. Like the standard ELISA method, HIV-1 particles were incubated with alkaline phosphatase (AP)-labeled broadly neutralizing antibody PGT128.…”
Section: Chinese Researchers Have Introduced a Pcr-based Crispr-cas13amentioning
confidence: 99%
See 1 more Smart Citation
“…147 (C) PCR-based CRISPR-Cas13a system. 171 (D, E) A highly efficient microfluidic droplet-based platform to screen single virus particles for optimum vaccine candidate antigenic compounds. Like the standard ELISA method, HIV-1 particles were incubated with alkaline phosphatase (AP)-labeled broadly neutralizing antibody PGT128.…”
Section: Chinese Researchers Have Introduced a Pcr-based Crispr-cas13amentioning
confidence: 99%
“…CD4+ T cells were washed and mixed 1:1 with ddPCR master mix and cell lysis agent. Droplets generated, and cells are lysed inside the droplets, followed by PCR amplification of Tat‐Rev spliced or unspliced cell‐associated HIV‐1 RNA 170 . The schematic diagram shows a rapid, targeted, and culture‐free viral infectivity assay in drop‐based microfluidics.…”
Section: Introductionmentioning
confidence: 99%
“…A novel ctDNA biomarker released from HBV-related HCC tumors was recently proposed to overcome these limitations, namely, the circulating DNA fragment generating from the junctions of HBV integration in the chromosomes of HCC. This virus–host chimera DNA (vh–DNA) consists of the junctional fragments at the HBV integration site, containing both virus and human DNA sequences [ 149 ]. Since the randomly distributed HBV DNA integrations have been identified in ~90% of HBV-related HCC [ 19 ], the integration-derived vh–DNA can be applied as a biomarker for detecting the majority of HBV–HCC.…”
Section: Diagnosis Of Hbv-related Hcc By Circulating Virus–host Chimera Tumor Dna Generated By Hbv Integrationmentioning
confidence: 99%
“…At the same time, their detection levels correlated with the tumor sizes (with detection limit at 1.5 cm diameter). By monitoring the residual circulating vh–DNA in the blood collected after surgery, 90% of the patients with detectable vh–DNA levels in 2 months postsurgery experienced HCC recurrence within 1 year [ 149 ]. Therefore, the vh–DNA generated by HBV integration might become a new circulating ctDNA biomarker for detecting the tumor load in most HBV-related HCC patients.…”
Section: Diagnosis Of Hbv-related Hcc By Circulating Virus–host Chimera Tumor Dna Generated By Hbv Integrationmentioning
confidence: 99%
“…A study of 20 people with HBV-HCC found circulating vh-DNA representing 87 different HBV integration sites, which were enriched in genes involved in cancer-related pathways, suggesting they could act as a biomarker for HCC diagnosis (Li et al, 2019). Moreover, Li et al (2020) detected vh-DNA in 97.7% of people with HBV-related HCC. Two months following HCC resection, the same vh-DNA sequence could be detected in 10 cases (23.3%), nine of whom (90%) experienced HCC recurrence within a year.…”
Section: Hcc Recurrencementioning
confidence: 99%